Numerical Simulation Analysis of Dam Breaks using ISIS & HEC-RAS - Almassri, Belal (My University, 2011)
Numerical Modelling is one of the most information-dependent researches compared to other sectors. Computers have been used to improve the efficiency of management in most of the engineering projects including the disaster recovery processes. Treating information efficiently is the key to maintain a high degree of the security for all of the engineering projects. This research presents the numerical analysis of different simulation cases related to different types of modelling tests using two of the leading softwares in the river modelling field which are the ISIS and the HEC-RAS, these cases present two of the dam failure tests, the simulation of the river flood, the dry bed river and the sinusoidal oscillation case. This research gives also fully understanding steps for the two softwares from the starting up of the programs and finishing with the results and the discussions. The research also highlights a comparison of the results of this research and other results from previous researches then it highlights a comparison between the ISIS and the HEC-RAS in order to decide which one is more efficient, faster and more reliable than the other. From the simulation analysis done in this research it presents some more advantages in the HEC-RAS which they are not exist in the ISIS however the ISIS can be more efficient and gives more reliable results if a different type of simulation cases were applied or different size of data has been inserted into the programs so for these reasons this research suggests more investigations to be done in the future studies before carrying on the simulation processes with different types of cases and large amounts of data in order to decide which software is more efficient than the other. Keywords: ISIS; HEC-RAS; Steady State Analysis; Unsteady State Analysis; Upstream Boundary Condition; Downstream Boundary Condition; Flow Hydrograph; Stage Hydrograph.
Keywords: HecRas-ISIS-Dam Break Analysis